SINKRONISASI TABEL BERBASIS RECORD MENGGUNAKAN SISTEM KEAMANAN AUTHENTICATION, AUTHORIZATION, ACCOUNTING (AAA) (STUDI KASUS DI STTA YOGYAKARTA) - Suwito Suwito; Hero Wintolo; Dwi Nugraheny (Institut Teknologi Dirgantara Adisutjipto, 2012)
Synchronization is the process of setting the course of several processes at the same time. Synchronization builds upon students' academic value table STTA Yogyakarta by comparing records for the records in the database. If there is a difference in the academic value of the table the different values will be returned as the value of the original with comparing by using the master database. Record based table synchronization is expected to address the security system on the database and provide security guarantees a safe and comfortable.Authentication is a process by which a user is identified by the server before the user using the network. In the process, the user is requesting access rights to the server to use a network. Authorization is the allocation of what services are entitled to be accessed by the user on the network. Authorization is done when the user has been declared eligible to use the network. Accounting is a process performed by the server to record all user activity in the network, such as when the user starts using the network, end user when the connection to the network, how long the user using the network, how much data is accessed from the network user.The results of the implementation of synchronization using a table based record system security authentication, authorization, accounting changes that may prevent the occurrence of data in a database, optimizing the use of stored, and enhance security systems at the database STTA center of Yogyakarta.